Geotouristic interpretive trail in the Serra de São José in the vicinity of "estrada real" / MG - Pereira, Milla Barbosa; Ferreira, Arlon Cândido; Rocha, Leonardo Cristian (Anuário do Instituto de Geociências, 2012)
The study was developed on a trail known as the "trail of slaves" in the mountains of São José, Tiradentes city, Minas Gerais State, Brazil. This place has major lithological and pedological variations, besides historical importance. The access to the trail is easy along 1,356m in length. The mapping permitted to identify the geological aspects which are essentials for the dissemination of the geological heritage, geoconservation and geotourism.